Topical problems of diabetes treatment during pregnancy - Irina Yur'evna Demidova; Natalya Yur'evna Arbatskaya; Elena Petrovna Mel'nikova (Сахарный диабет)
The main causes behind decompensation of diabetes mellitus (DM) in pregnant women are consid-ered, such as metabolic and hormonal disturbancesinfluencing insulin requirement in different periods of pregnancy and variability of glycemia related to pharmacokinetic and pharmacodynamicproperties of insu-lin preparations. Recommended target levels of glycemia in pregnant women with DM are cited. The fre-quencyof self-monitoring blood glucose and principles of intensive insulin therapy are discussed. Advan-tages of continuous subcutaneous insulin infusionand its role in the maintenance of stable control of car-bohydrate metabolism during pregnancy are discussed.